Delineation of distinct subgroups of multiple myeloma and a model for clonal evolution based on interphase cytogenetics - Cremer, Friedrich Walter; Bila, Jelena; Buck, Isabelle; Kartal-Kaess, Mutlu; Hose, Dirk; Ittrich, Carina; Benner, Axel; Raab, Marc-Steffen; Theil, Ann-Cathrin; Moos, Marion; Goldschmidt, Hartmut; Bartram, Claus R.; et al. (Genes, chromosomes & cancer, 2005)
To delineate multiple myeloma (MM) subgroups and their clonal evolution, we analyzed 81 newly diagnosed patients by interphase fluorescence in situ hybridization using a comprehensive probe set for 10 chromosomes and two IGH rearrangements. A median of 5 probes per patient displayed aberrant signal numbers (range, 1-10). Additional copies most frequently found were for 15q22, 19q13, 9q34, 11q23, and 1q21. Losses commonly observed were of 13q14.3, 17p13, and 22q11. Predominance of gain or loss was quantified by a copy number score (CS) for each patient. Two peaks (CS = +3 and CS = 0) were found by plotting patient copy number scores over CS values corresponding to hyperdiploid and nonhyperdiploid MM. Cluster analysis revealed four major branches: (i) gain of 9q, 15q, 19q, and/or 11q; (ii) deletion of 13q and t(4;14); (iii) t(11;14); and (iv) gain of 1q. Statistical modeling of an oncogenetic tree indicated that early independent events were gain of 15q/9q and/or 11q, t(11;14); deletion of 13q followed by t(4;14); and gain of 1q. Aberrations of 17p13, 22q11, 8p12, and 6q21 were found as subsequent events. MM with gain of 1q was delineated as a subentity with significantly higher beta-2-microglobulin and lower hemoglobin levels, indicating a poor prognosis. From our results, we propose a model of MM for clonal evolution. © 2005 Wiley-Liss, Inc.